Introducing the New Indices of God Images (NIGI): Distinguishing between God of Grace and God of Law - Francis, Leslie J. (Journal of empirical theology, 2025)
Building on a stream of research initiated by Benson and Spilka (1973) and drawing on insights afforded by empirical theology, the present study introduces the New Indices of God Images (NIGI) designed to distinguish between two divergent theological concepts of God, construed as God of Grace and God of Law, and each operationalised by brief three-item scales. Data provided by 5,269 students between the ages of 13 and 15 years who professed belief in God demonstrated good levels of internal consistency reliability for these two orthogonal measures. Construct validity for the two measures was established alongside measures of self-esteem (images of self) and of empathy (images of others). Higher scores on the Index of God of Grace were associated with higher self-esteem and higher empathy. Higher scores on the Index of God of Law were associated with lower self-esteem and lower empathy.